Antibacterial and antibiofilm effect of moringa oleifera leaves on bacteria associated with endodontic-periodontal lesions: an experimental study - Darma, Joshua; Amin, Meiny Faudah; Elline, Elline; Komariah, Komariah; Kurnia, Dikdik (Universitas Padjadjaran, 2025)
Introduction: Sodium hypochlorite (NaOCl) is the gold standard irrigation solution in root canal treatment; however, its clinical use is limited by its potential toxicity to periodontal tissue. Moringa oleifera is a natural plant known for its antibacterial properties. The study aims to analyze the potential antibacterial and antibiofilm effects of M. oleifera leaves on bacteria associated with endodontic-periodontal lesions. Methods: An experimental study was conducted using samples of P. gingivalis ATCC 33277 and S. sanguinis ATCC 10556 cultured on BHI agar before exposure to M. oleifera leaf extract at concentrations of 80, 60, 40, and 20%. A 5.25% NaOCl solution served as the positive control, while distilled water was used as the negative control. The minimum inhibitory concentration (MIC) was determined using the tube dilution method with BHI medium and defined as the lowest concentration that inhibited bacterial growth. The minimum bacterial concentration (MBC) was determined by subculturing inoculum from tubes that showed no visible growth in the MIC test. A standard plate count method was used to measure the growth density of P. gingivalis and S. sanguinis. The antibiofilm assay evaluated biofilm attachment using crystal violet staining. Biofil density was quantified using spectrophotometry at 570nmto measure the amount of transmitted light. A One-way ANOVA Test was applied to the normally distributed data, while the Kruskal-Wallis Test was used for non-normally distributed data. Post-hoc tests were performed to determine significant differences between groups, with a significance level set at p < 0.05. Result: The antibacterial test showed a significant effect of M. oleifera leaf extracts on the elimination of P. gingivalis (p = 0.002) and S. sanguinis (p = 0.001). The antibiofilm tests also showed a significant difference between among M. oleifera extract groups. Conclusion: M. oleifera leaf extract at concentrations of of 60 and 80 % exhibits antibacterial and antibiofil effects against P. gingivalis and S. sanguinis.